PENGARUH PENAMBAHAN ASAM SITRAT PADA EKSTRAKSI DAUN JATI (Tectona grandis Linn.f.) TERHADAP SIFAT FISIK SEDIAAN SHEER LIPSTICK - Mikhania C.E., Kukuh Judy Handojo, Lailatul Fitriyah (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2017)
The aim of this study was to know the influence of citric acid addition on teak leaf (Tectona grandis Linn.f.) extraction to the physical properties of sheer lipstick. Physical properties of sheer lipstick include organoleptic test and pH test. The result data for organoleptic test of sheer lipstick color using teak leaves extracted with 3% citric acid addition (F1) was yielded pink, 5% (F2) was red and 7% (F3) was dark red. The organoleptic test of the aroma from three formulas has the same particular odor of essence strawberry. Data of pH test result from three formulations of sheer lipstick using teak leaves extracted with 3% citric acid (F1) was 3,867 ± 0,115, 5% (F2) was 3,467 ± 0,208 and 7% (F3) was 3,233 ±0,057. Data analysis of pH using One Way Anova obtained significance value 0,004 (p 0,05) therefore can be interpreted that there was significant difference of pH from all formulation. From the results it can be concluded that the preparation sheer lipstick using teak leaf extract with addition of citric acid 3%, 5% and 7% influence physical properties of color and pH, but didn’t influence odor.Keywords: citric acid, teak leaf, sheer lipstick